Decoupling of CO2, CH4, and N2O agriculture emissions in the EU - Jean Vasile Andrei; Sorin Avram; Irina Băncescu; Irina Băncescu; Ioan I Gâf Deac; Carmen Adriana Gheorghe; Anișoara Ionela Diaconu (Frontiers in Environmental Science, 2022)
This research addresses the problem of CO2, CH4, and N2O emissions in the EU for the 2008–2018 period, and their contributing factors, through extensive and complex analysis. The research incubated in the manuscript answers the question of whether new state members managed to catch up with old state members regarding technology innovation and mitigation of N2O emissions from agriculture activities. The methodology used includes Tapio decoupling index and the metafrontier non-radial Malmquist N2O emission performance index. The research considers short-term, medium-term, and long-term decoupling analyses. Results suggest a shift of decoupling status is worse for the 2013–2018 period compared to the 2008–2013 period which should concern low-carbon agriculture policy-makers. Also, it was noticed an increase in total-factor N2O emission performance for the 2008–2018 period. New state members managed to catch up with old state members regarding technology innovation and mitigation of N2O emissions from agricultural activities; however, not all countries managed to do so. For example, Romania has experienced an efficiency loss due to a technology change and from this perspective, Romania should address first managing N2O and CO2 emissions. The findings extend the traditional framework of investigating the effects of CO2, CH4, and N2O in agriculture and highlight the necessity of addressing environmental aspects from a broader perspective of the policymakers and in developing innovative decoupling indexes. The research investigation is reporting from a post-transition country by prioritizing the measures to be implemented.